The determinants of credit risk in conventional bank in Malaysia - Md Nazir, Nur Rahimah (2015)
This study investigates the relationship between bank-specific variables (BSV) and credit risk in conventional banks in Malaysia. The research uses credit risk as the dependent variable, while the independent variables are loan expansion (LOAN EXP), loan quality (LOAN QUA), capital buffer (CAP BUF), capital ratio (CAP RAT), and bank size (B. SIZE). The study employed an annual sample from 2005 to 2014, with data collected from the BankScope database. Using a panel data analysis, the results indicate that loan quality has a positive relationship with credit risk, while bank size has a negative relationship.